NONCODEV6: an updated database dedicated to long non-coding RNA annotation in both animals and plants. Issue Volume 49:Issue D1(2021) (16th November 2020) - Zhao, Lianhe; Wang, Jiajia; Li, Yanyan; Song, Tingrui; Wu, Yang; Fang, Shuangsang; Bu, Dechao; Li, Hui; Sun, Liang; Pei, Dong; Zheng, Yu; Huang, Jianqin; et al.
Abstract: NONCODE (http://www.noncode.org/ ) is a comprehensive database of collection and annotation of noncoding RNAs, especially long non-coding RNAs (lncRNAs) in animals. NONCODEV6 is dedicated to providing the full scope of lncRNAs across plants and animals. The number of lncRNAs in NONCODEV6 has increased from 548 640 to 644 510 since the last update in 2017. The number of human lncRNAs has increased from 172 216 to 173 112. The number of mouse lncRNAs increased from 131 697 to 131 974. The number of plant lncRNAs is 94 697. The relationship between lncRNAs in human and cancer were updated with transcriptome sequencing profiles. Three important new features were also introduced in NONCODEV6: (i) updated human lncRNA-disease relationships, especially cancer; (ii) lncRNA annotations with tissue expression profiles and predicted function in five common plants; iii) lncRNAs conservation annotation at transcript level for 23 plant species. NONCODEV6 is accessible through http://www.noncode.org/ .